2021
DOI: 10.1155/2021/9525062
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Basketball on Improving the Health of Obese People under the Monitoring of Internet of Things Technology

Abstract: By accelerating the aforementioned industrialisation and urbanisation, people’s way of life has undergone enormous changes. The incidence of overweight and obesity increases rapidly. This research first broke through the impact of basketball on improving physical health and then designed experiments separately. The experiment is divided into two experimental groups and a replacement group, with 150 people in total, 50 people per group, excluding the interference of gender, age, and other factors. The influenci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…It demonstrates that a 12-week exercise intervention in the form of running using running APP software can help students improve their vital capacity. (3) e APP intervention has a clear effect on improving the vital capacity of male students. It effectively slowed the decline in female students' vital capacity to some extent.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…It demonstrates that a 12-week exercise intervention in the form of running using running APP software can help students improve their vital capacity. (3) e APP intervention has a clear effect on improving the vital capacity of male students. It effectively slowed the decline in female students' vital capacity to some extent.…”
Section: Discussionmentioning
confidence: 96%
“…Jiang et al's survey of college students shows that 89.3% of boys like physical exercise, 68.1% of girls like physical exercise, and 10.7% of boys feel below average; girls accounted for 30.6%, which shows that girls' interest in physical exercise is slightly worse than that of boys [2]. Liu et al pointed out that most students hold a good attitude toward exercise, but according to grades, the scores of exercise attitude vary from grade to grade, and the scores of lower grades are generally better than those of higher grades [3]. Kim et al found through the experimental intervention of aerobics that aerobics has a positive e ect on improving the oxidation strength of body fat.…”
Section: Introductionmentioning
confidence: 99%
“…From the feedback questionnaire of coaches and athletes, the most common methods adopted by coaches are the training method to avoid aggravating the injury and the strength exercise to strengthen the injured part, and the proportion is nearly 90%, which indicates that the training of trainers in the rehabilitation stage after the injury of athletes is mainly to avoid aggravating the injury and then strengthen other training of the injured part, hoping that the injured part of the athlete will not be degraded or other adverse effects due to the rest of the rehabilitation period. And in part of the athletes, it is give priority to in order to strengthen the power of the injured area to practice and strengthen the core strength training proportion similar to avoid aggravating the proportion of pain, showing athletes in convalescence after injury; choose the injured parts of the relevant training, to maintain the quality of their own body condition and to avoid physical injury [ 21 ]. It can be found from the feedback of these two degrees that sports injury has a great impact on athletes, even the whole sports team, and has a certain impact on the athletes' competitive state.…”
Section: Experiments and Analysismentioning
confidence: 99%
“…With the help of Internet of ings technology, the scientific and technological content of ecological environmental monitoring can be improved, and the efficiency of ecological environment monitoring can be improved. At the same time, it can relatively reduce the detection pressure of environmental monitoring personnel [6].…”
Section: Introductionmentioning
confidence: 99%